Putting Single Session Thinking to Work: Conceptual, Practical, Training, and Implementation Ideas. Issue 3 (13th October 2020) - Young, Jeff
Abstract : There is growing pressure on health and welfare services to provide more efficient and effective services. For one thing, the world's ageing population is resulting in increased pressure on healthcare costs and the availability of government funding. At the same time, community expectations of quick and easy access to high‐quality client‐centred services is growing. Single session ideas can make a valuable contribution to responding to these somewhat competing factors, by providing a basis for effective, efficient, client‐centred, accessible services. This article begins with a functional definition and description of single session therapy (SST), which is used to inform article sections on the attitudinal, clinical, and organisational implications, and ends with ideas for implementing the approach into services, thus, putting SST to work.